Non-planar backbone structure polybenzimidazole membranes with excellent solubility, high proton conductivity, and better anti-oxidative for HT-PEMFCs. Issue 93 (23rd September 2016) - Sun, Guohua; Han, Kefei; Yu, Jinghua; Zhu, Hong; Wang, Zhongming
Abstract : This work introduces a bulky stereostructure monomer (BPY) to obtain a series of novel non-planar BPY-PBI- x polymers, which exhibit excellent solubility, high proton conductivity, and better anti-oxidative for HT-PEMFCs. Abstract : As an efficient, inexpensive, readily accessible monomer of the polybenzimidazole (PBI) copolymer, the 4, 4′-[(4, 4′-bipyridine)-2, 6-diyl]dibenzoic acid (BPY) containing bipyridine unit was firstly used to synthesize a series of novel non-planar PBI copolymers (BPY–PBI- x ) by regulating the ratio with 2, 6-pyridinedicarboxylic acid under microwave-assisted conditions. The copolymers exhibit superior solubility in aprotic solvents such as N, N -dimethylacetamide, N, N -dimethylformamide and dimethylsulfoxide than general PBI, and the corresponding BPY–PBI- x serial membranes were prepared by a solution casting method. All the membranes have been characterized by thermal stability, a tension test, scanning electron microscopy, PA-doping ability and swelling ratio, proton conductivity, and a Fenton test. The membranes exhibit excellent comprehensive properties containing high proton conductivity and long lifetime. The conductivity of the doping levels of the BPY–PBI-100% membrane with the highest doping level (342.7%) reaches 78.6 mS cm −1 at 160 °C. The high proton conductivity is attributed to the increase in N atoms of the proton acceptor from the bipyridine monomer and the enhancement of free volume from the existence of a bulky stereostructure BPY unit. The long lifetime is due to the fact that the pyridine unit can quench radicals by the formation of pyridine-N-oxide. The unique anti-oxidation mechanism of the BPY–PBI- x serial membranes, which firstly was pointed out for the application of pyridine heterocyclic rings in HT-PEMs, provides new insights for novel anti-oxidation membrane design. In short, 3-fold objectives, namely, (I) soluble PBI, (II) higher proton conductivity PBI, and (III) anti-oxidative PBI, were achieved in this paper.